Application of Online to Offline health education in the school for pregnant women on health literacy of pregnant women (基于OTO模式的孕妇学校健康教育提高孕妇母婴健康素养的效果研究) - MIN Min (闵敏); XING Cui (邢翠) (中西医结合护理)
Objective To explore the effect of health education based on OTO model in the school for pregnant women on health literacy of pregnant women. Methods Totally 145 outpatient pregnant women who were examined between August and September 2020 were treated as control group, and were given routine health education. Another 137 outpatient pregnant women who were examined in October to November 2020 were treated as study group, and the health education based on OTO as well as the routine health education was given. The health literacy of the two groups was compared, and the satisfaction degree of pregnant women was evaluated. Results The health literacy score of pregnant women in the study group was higher than that in the control group (P<0. 01). The satisfaction rate in the study group was higher than that in the control group (P<0. 01). Conclusion OTO-assisted health education in the school for pregnant women school is potentially effective to improve the health literacy of pregnant women. (目的 构建基于OTO模式的孕妇学校教育模式, 探讨其提高孕妇健康素养的教育效果。方法 选择2020年8月—9月门诊产检的孕妇145例为对照组, 给予常规健康教育; 将2020年10月—11月门诊产检的孕妇137例设为研究组, 在常规健康教育的基础上, 基于OTO模式, 增加线上平台的门诊孕妇学校健康教育。对比2组孕妇的母婴健康素养及满意度, 评价教育效果。结果 研究组孕妇的健康素养得分和满意度明显高于对照组, 差异有统计学意义(P＜0. 01)。结论 基于OTO模式的孕妇学校教育, 有助于孕妇健康素养和满意度的提高。)